Characterization and safety assessment of Hydroxypropyl Musa paradisiaca starch for pharmaceutical applications - Samyuktha Metta, Suvendu Kumar Sahoo (Journal of Applied Pharmaceutical Science, 2024)
The aim of the current investigation was to produce native banana starch (NBS) and hydroxypropyl banana starch (HPBS) , assess physicochemical properties, and evaluate toxicity. NBS was modified to its propyl form with a propylene oxide solution and characterized. The physicochemical properties of NBS and HPBS met the required specifications. The amylose content of NBS was found to be 25.41% ± 0.08%. The degree of substitution and hydroxyl propyl group % were found to be 0.028 and 2.894, respectively, which were within the Food and Drug Administration’s (FDA’s) acceptable limits of 0.2% and 7%, respectively. The NBS possesses superior swelling power (26.68 ± 1.06) compared to the HPBS swelling power (15.66 ± 0.61). In terms of soluble starch content (%), HPBS displayed a higher soluble starch content percentage (69.21 ± 2.04) compared to the NBS (17.01 ± 1.06). The HPBS yielded high viscosity relative to the NBS in all the concentrations of starch solutions. The increase in the soluble starch content and viscosity of propyl starch may be attributed to the increased number of hydroxy propyl group substitutions in the HPBS. For up to 14 days of the experimental period in the acute toxicity studies, the rats showed no symptoms of toxicity or fatalities. According to the findings of the subacute toxicity studies, neither the hematological nor the biochemical analyses showed any apparent abnormalities. The study’s overall results show that HPBS were safe up to doses of 1,000 mg/kg body weight, which may be regarded as a safe dosage. The modified starch’s enhanced physicochemical properties make it suitable for industrial use, and it meets FDA-approved limits, affirming its safety as a pharmaceutical excipient.
Keywords: Native banana starch, hydroxypropyl banana starch, degree of substitution, acute toxicity, subacute toxicity